IncC blaKPC-2-positive plasmid characterised from ST648 Escherichia coli. (December 2019) - Papagiannitsis, Costas C.; Bitar, Ibrahim; Malli, Ergina; Tsilipounidaki, Katerina; Hrabak, Jaroslav; Petinaki, Efthimia
Highlights: Complete genome of ST648 Escherichia coli was characterised using the Sequel platform. bla KPC-2 was carried on ARI-B resistance islands of type 2 IncC plasmids. MDR regions were inserted into orfA of IncB plasmids pB-Ec2 and pB-Ec20. First report on acquisition of Tn 4401a by an IncC replicon. Results underline the increasing clinical importance of the IncC plasmid family. Abstract: Objectives: This study describes the characterisation of type 2 IncC plasmids pC-Ec20-KPC and pC-Ec2-KPC, carrying the bla KPC-2 gene, from two multiresistant Escherichia coli recovered in University Hospital of Larissa (Greece) in 2018. Methods: E. coli strains Ec-2Lar and Ec-20Lar were recovered from rectal swabs of two patients during monthly surveillance cultures. Transfer experiments by conjugation were carried out using rifampicin-resistant E. coli A15 laboratory strain as recipient. bla KPC -carrying plasmids were characterised by S1 profiling. Isolates were typed by MLST. Whole-genome sequencing was performed using the Sequel platform. Results: Both E. coli isolates, belonging to ST648, transferred bla KPC-2 to E. coli A15 by conjugation. Plasmid analysis revealed that the transconjugants harboured bla KPC -positive plasmids of different sizes. Analysis of plasmid sequences showed that in both isolates the bla KPC-2 gene was carried on a type 2 IncC plasmid (pC-Ec20-KPC and pC-Ec2-KPC, respectively). Both plasmids carried the ARI-B resistance island consisting of several resistance genes, intact and truncated copies of several mobile elements, and a 25 571-bp segment harbouring coding sequences for an iron transporter. The bla KPC-2 gene was part of transposon Tn 4401a, which was bounded by 5-bp direct repeats (TCCTT) suggesting its transposition into the IncC plasmids. Conclusion: To our knowledge, this is the first report on complete nucleotide sequences of type 2 IncC plasmids. These findings, which hypothesise the acquisition of KPC-2-encoding transposon Tn 4401a by an IncC replicon, indicate the ongoing need for molecular surveillance studies of multidrug-resistant pathogens. In addition, they underline the increasing clinical importance of the IncC plasmid family.